Renal effects of inhaled nitric oxide in humans. - Wraight, WM; Young, J (2001)
We measured renal sodium and water excretion in five healthy male volunteers who inhaled nitric oxide. Urine volumes, urinary sodium and creatinine, and plasma sodium and creatinine were measured before, during and after a 2-h period inhaling nitric oxide (40 vpm in air). A control experiment, excluding the nitric oxide, was done on a separate day. Nitric oxide increased urinary volume (mean increase 85%, SEM 22%) and prevented a decrease in fractional excretion of sodium (32% SEM 8%) seen in the control experiments, without a detectable change in creatinine clearance. The results suggest the inhaled nitric oxide may alter tubular salt and water resorbtion in humans. The mechanism for this remains unclear.